Materials on Plant Leaf Surfaces Are Deliquescent in a Variety of Environments - Tredenick, E. C.; Stuart-Williams, H.; Enge, T. G. (Frontiers in Plant Science, 2022)
}Materials on plant leaf surfaces that attract water} impact penetration of foliar-applied agrochemicals, foliar water uptake, gas exchange and stomatal density. Few studies are available on the nature of these substances, and we quantify the hygroscopicity of these materials. Water vapor sorption experiments on twelve leaf washes of sample leaves were conducted and analyzed with inductively coupled plasma-optical emission spectroscopy and X-ray diffraction. All leaf surface materials studied were hygroscopic. Oils were found on the surface of the Eucalyptus studied. For mangroves that excrete salt to the leaf surfaces, significant sorption occurred at high humidity of a total of 316~mg ($\sim$0.3~mL) over 6--10 leaves, and fitted a Guggenheim, Anderson, and de Böer sorption isotherm. Materials on the plant leaf surface can deliquesce and form an aqueous solution in a variety of environments where plants grow, including glasshouses and by the ocean, which is an important factor when considering plant-atmosphere relations.